2019
DOI: 10.4028/www.scientific.net/amm.895.76
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Effect of Cryogenic Temperature on Mechanical Behavior of Jute and Hemp Fibers Reinforced Polymer Composites

Abstract: In past few decades, natural fibers which are viable and abundant in nature are the emerging trends in material science as reinforcement for polymer matrix materials and they are the commute for the non-biodegradable, non-renewable and high-density synthetic fibers. Plant-based fibers such as banana, hemp, kenaf, PALF, jute, and coir has been used as reinforcement in a polymer matrix for the applications in consumer goods, furniture’s, civil and automotive structures and low-cost housing structures. The natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…They showed that hemp/epoxy composites could compete with glass/epoxy composites. The covers for ultra-light airplanes produced for the purpose of the tests showed very good properties and, at the same time, greater environmental friendliness [ 134 ]. As indicated by previous research and theory, natural fibers require some modification to improve compatibility with the polymer matrix.…”
Section: Hemp and Derivatives In The Polymer Industrymentioning
confidence: 99%
“…They showed that hemp/epoxy composites could compete with glass/epoxy composites. The covers for ultra-light airplanes produced for the purpose of the tests showed very good properties and, at the same time, greater environmental friendliness [ 134 ]. As indicated by previous research and theory, natural fibers require some modification to improve compatibility with the polymer matrix.…”
Section: Hemp and Derivatives In The Polymer Industrymentioning
confidence: 99%
“…Hal ini juga dibuktikan dengan bentuk patahan benda kerja seperti ditunjukkan pada Gambar 6. Dari hasil yang dicapai juga disampaikan senada dalam penelitian yang dilakukan oleh [29][30][31][32] , dimana dijelaskan bahwa temperatur besar pengaruhnya terhadap sifat bending dari material komposit baik berbahan dasar serat organic maupun serat inorganic [33] . Keunggulan dari treatment pada low temperature juga meningkatkan interfacial bending strength sebesar 31%.…”
Section: Three-point Bending Pada Pipa Kompositunclassified
“…24 In general, physicochemical/thermal treatments on the composites create micro-cracking on its surface, making it more susceptible to moisture and brittle failure. 25…”
Section: Introductionmentioning
confidence: 99%
“…24 In general, physicochemical/thermal treatments on the composites create micro-cracking on its surface, making it more susceptible to moisture and brittle failure. 25 There is a dearth of research on the cryogenic treatment of natural fibres before the consolidation of composite and its impact on fibres characteristics and behaviour of subsequently fabricated composites. This investigation deals with the cryogenic treatment of hemp fibres before the consolidation of composites, its influence on fibre characteristics and subsequently fabricated composites with treated fibres.…”
Section: Introductionmentioning
confidence: 99%